(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a kind of distributed computing over the internet i.e. it can run a program or application on more than one computer at the same time. It is divided into three categories namely: (i) Infrastructure as a service (IaaS), (ii) Platform as a service (PaaS), and (iii) Software as a service (SaaS). Software as a service is a kind of service which provides many benefits to the service consumers. A customized quality model is necessary to evaluate the quality of SaaS cloud service. In this paper we identify the features of SaaS. The traditional quality model does not consider features of SaaS like security and quality of service. So, In this paper, we propose a new quality model for the security, quality of service, and software quality for software as a service. Moreover the results are used as identification for the SaaS quality management